Εφαρμογή της Θεωρίας της Κάντερ και Ενδυνάμωση του Νοσηλευτικού Προσωπικού - Menikou, Joanna (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Empowerment has become an increasingly important factor in determining nurse burnout, work satisfaction, performance and effectiveness in their work. Aim: The purpose of this study was to test Kanter’s theory of organizational power at nursing work environment. Method: The search of relevant articles was performed using the database PUBMED with two techniques: a) by using the keywords: “Kanter’s theory of structural power in organizations”, “organizational empowerment”, “job satisfaction”, “burnout”, “psychological empowerment”, “structural empowerment” and “emotional exhaustion”, with all the possible combinations, and b) by using the author’s name: “Laschinger”. The final sample consisted of 11 studies. Results: Consistent with theoretical expectations, perceptions of formal and informal power significantly influenced perceived access to work empowerment structures. Empowerment was significantly related to occupational stress, burnout, control over nursing practise, autonomy, work satisfaction and effectiveness. Finally, the strongest empowerment factor was the access to the structures of opportunity. Conclusions: The studies support the Kanter’s theory of structural power in organizations. The empowerment of staff nurse is an important factor in creating a work environment which supports the professional nursing practise.
Keywords: Employee empowerment; Burnout, Professional